HUBUNGAN FAKTOR LINGKUNGAN DAN GAYA HIDUP DENGAN ANGKA KEJADIAN TONSILITIS DI PUSKESMAS SIMALINGKAR - Sihombing, Rombadi Y; Tobing, Jerry; Marpaung, Alexander P (Jurnal Kedokteran Methodist, 2022)
Background: Tonsillitis is a disease that is often found in both children and adults, but is more common in the younger age group. This disease can occur due to repeated attacks of acute tonsillitis which can eventually cause changes or permanent damage to the tonsil tissue. Methods: The design of this study used a case control design. The population of this study were all patients who experienced tonsillitis which was influenced by environmental and lifestyle factors at the Simalingkar Health Center Jalan Bawang Raya No. 37, Medan Tuntungan District. The research sample is 60 people. Research data collection was carried out based on primary and secondary data, namely data available through health center medical records. Analysis of research data consisted of univariate analysis, bivariate with Chi Square test. Results: The results showed that there was relationship between lifestyle factors (p = 0.00 < 0.05), environmental factors (p = 0,02 < 0.05) were significant to the incidence of tonsillitis. The incidence of tonsillitis is mostly experienced by the age of childhood aged 5-11 years as many as 21 people (35%) and the gender of the majority of women as many as 36 people (60%). Conclusion: There is relationship between lifestyle factors, environmental factors on the incidence of tonsillitis. The incidence of tonsillitis is mostly experienced by the age of childhood aged 5-11 years and female sex.